Methods of Model Based Process Control 1995
DOI: 10.1007/978-94-011-0135-6_12
|View full text |Cite
|
Sign up to set email alerts
|

State-Space Interpretation of Model Predictive Control

Abstract: A model predictive control technique based on a step response model is developed using state estimation techniques. The standard step response model is extended so that integrating systems can be treated within the same framework. Based on the modified step response model, it is shown how the state estimation techniques from stochastic optimal control can be used to construct the optimal prediction vector without introducing significant additional numerical complexity. In the case of integrated or double integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
14

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 14 publications
1
83
0
14
Order By: Relevance
“…However, as the name suggests, offline methods lead to overly conservative designs, and they are unsuitable to be employed in real-time as well as in conjunction with the MPC design [13,19].These are usually performed using computer simulations for all time stamps based on the employed scheduling algorithm. As far as Model predictive control is concerned, these offline computer simulations will prove too expensive.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, as the name suggests, offline methods lead to overly conservative designs, and they are unsuitable to be employed in real-time as well as in conjunction with the MPC design [13,19].These are usually performed using computer simulations for all time stamps based on the employed scheduling algorithm. As far as Model predictive control is concerned, these offline computer simulations will prove too expensive.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ever since MPC became popular with the chemical plants and process industries [13], significant research has gone into this area of control theory. However, there is still very little work which studies MPC operating over CAN with online delay analysis.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several control performance indexes are computed for different process configurations and compared in this section. Finally, the paper ends with some conclusions on the analyzed structures [23].…”
Section: Introductionmentioning
confidence: 96%
“…The MPC feedback and feedforward co-design procedure results in a tradeoff, where the controller tuning procedure is carried out taking into account the most important aspects. There exist several MPC formulations that can be used for disturbance compensation analysis providing the specific methodology in accordance with the analyzed features [17,22,23]. In [3,22,24], it was shown that the optimal MPC controller setup for disturbance attenuation results in high bandwidths in the feedback loop, and it is necessary to compensate this issue.…”
Section: Introductionmentioning
confidence: 99%